Measuring electron-positron annihilation radiation from laser plasma interactions. - Chen, H; Tommasini, R; Seely, J; Szabo, C; Feldman, U; Pereira, N; Gregori, G; Falk, K; Mithen, J; Murphy, C (2012)
We investigated various diagnostic techniques to measure the 511 keV annihilation radiations. These include step-wedge filters, transmission crystal spectroscopy, single-hit CCD detectors, and streaked scintillating detection. While none of the diagnostics recorded conclusive results, the step-wedge filter that is sensitive to the energy range between 100 keV and 700 keV shows a signal around 500 keV that is clearly departing from a pure Bremsstrahlung spectrum and that we ascribe to annihilation radiation.